Changes in pulmonary microvascular permeability accompanying re-expansion oedema: evidence from dual isotope scintigraphy. Issue 6 (June 1990) - Wilkinson, P D; Keegan, J; Davies, S W; Bailey, J; Rudd, R M
Abstract : The pathophysiological mechanism of pulmonary oedema following rapid re-expansion of a collapsed lung is poorly understood. It has been suggested that the period of collapse or subsequent reinflation produces an increase in pulmonary microvascular permeability. To investigate this, the pulmonary accumulation of the plasma protein transferrin was measured by radiolabelling it in vivo with indium-113m. Plasma protein accumulation was calculated after correcting the accumulation of transferrin for changes in intrathoracic blood distribution by simultaneously monitoring technetium-99m labelled red blood cells. Functional images of plasma protein accumulation were constructed for the lung fields on a pixel by pixel basis. Investigations were performed on 14 subjects after drainage of a pleural effusion (n = 9) or evacuation of a pneumothorax (n = 5), and on 11 control subjects. Plasma protein accumulation was greater over the regions of lung re-expansion (-0.1-9.6, mean 2.9 x 10(-3)/min) than over the corresponding region of the contralateral lung (-1.2-0.8, mean 0.01 x 10(-3)/min; p less than 0.001). Patients who had undergone re-expansion procedures also had significantly greater plasma protein accumulation than normal controls. Nine of the 14 patients in the re-expansion group had clearly identifiable areas of increased plasma protein accumulation that corresponded to the part of the lung that had been re-expanded; no regional abnormalities were recorded in the control group. These results suggest that the reinflated lung displays abnormal microvascular permeability.